Evaluation of the Quality of Iran's Tour Agencies' Websites - Jafari, Alireza (2008)
This research studies 44 of Iran's tour agencies' websites, using content analysis to identify their quality. The evaluation of the websites was conducted by quantitative content analysis of three main groups of variables known as general information, value-added services and technical quality. The three groups of variables for measuring the quality of websites in terms of general information, value-added services and technical quality were selected based on UNCTAD's initiative, Lexhagen's (2005) research and Thelwall's (2000) website quality evaluation criteria respectively. In this study, three different tables were devised to evaluate the websites. Each table contained a number of variables and the analysis of them led to answer the questions of this study. Six websites were examined in pretest in order to improve and refine the codes. The data were analyzed using the Statistical Package for Social Science (SPSS) and frequencies and percentages were used to summarize the data. The results showed that the agencies' websites carried unequal attention to the quality factors studied in this research. While the majority of the websites presented rich technical quality, they did not have a good performance regarding value-added services, meaning that none of the websites could present rich value-added services. Besides, more than half of the websites were categorized as medium, in terms of general information. It was also observed that half of Iran's tour agencies' websites did not meet the characteristics of a high-quality website.